Power quality disturbance data compression, detection, and classification using integrated spline wavelet and S-transform - Dash, P.K.; Panigrahi, B.K.; Sahoo, D.K.; Panda, G. (2003)
In this paper, power quality transient data are compressed and stored for analysis and classification purposes. From the compressed data set, original data are reconstructed and then analyzed using a modified wavelet transform known as S-transform. Compression techniques using splines are performed through signal decomposition, thresholding of wavelet transform coefficients, and signal reconstruction. Finally, we present compression results using splines and examine the application of splines compression in power quality monitoring to mitigate against data-communication and data-storage problems. Since S-transform has better time frequency and localization property, power quality disturbances are detected and then classified in a superior way than the recently used wavelet transform.